2020
DOI: 10.33073/pjm-2020-013
|View full text |Cite
|
Sign up to set email alerts
|

Oligotrophic Nitrification and Denitrification Bacterial Communities in a Constructed Sewage Treatment Ecosystem and Nitrogen Removal of Delftia tsuruhatensis NF4

Abstract: Oligotrophic nitrifiers and denitrifiers play important roles in the removal of nitrogen from wastewater. Here, we studied the dominant bacterial populations of the sewage treatment ecosystem (STE) water from different processes and those of culture on oligotrophic heterotrophic nitrification (OHN) medium and oligotrophic aerobic denitrification (OAD) medium, using co-analysis of Illumina HiSeq DNA sequencing and traditional culture methods. The results showed that the STE water had no dominant population of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
3
6
0
Order By: Relevance
“…Next, we showed that S. rubidaea ED1 grew on a N-free solid medium supporting its oligonitrophilic feature (Table 1) as previously reported in Serratia liquefaciens and Serratia marcescens [81,82]. Indeed, oligonitrophilic bacteria have broad substrate specificities that allow them to maintain their structure in low N environments [83]. However, other environmental factors, such as soil pH, could greatly influence the oligonitrophilic function [84].…”
Section: Discussionsupporting
confidence: 81%
“…Next, we showed that S. rubidaea ED1 grew on a N-free solid medium supporting its oligonitrophilic feature (Table 1) as previously reported in Serratia liquefaciens and Serratia marcescens [81,82]. Indeed, oligonitrophilic bacteria have broad substrate specificities that allow them to maintain their structure in low N environments [83]. However, other environmental factors, such as soil pH, could greatly influence the oligonitrophilic function [84].…”
Section: Discussionsupporting
confidence: 81%
“…The second most frequent group in our study belonged to the family Xanthomonadaceae , but these bacteria were much more prevalent in sample B (12.43%), whereas in sample A their share was 4.70% and it was smaller than that of genus Burkholderia (5.88%) and family Rhodospirillaceae (5.35%). Members of Xanthomonadales were also found by Yang et al [ 47 ] in the experimental sewage treatment ecosystem in relative abundances ranging from 10.5 to even 78%. These are bacteria capable of performing heterotrophic denitrification, similar to the members of Burkholderiales [ 41 ], which were also found by Yang et al [ 47 ] among the top three most abundant populations in one of the samples derived from experimental sewage treatment system with a relative abundance of 9.9%.…”
Section: Resultssupporting
confidence: 71%
“…Members of Xanthomonadales were also found by Yang et al [ 47 ] in the experimental sewage treatment ecosystem in relative abundances ranging from 10.5 to even 78%. These are bacteria capable of performing heterotrophic denitrification, similar to the members of Burkholderiales [ 41 ], which were also found by Yang et al [ 47 ] among the top three most abundant populations in one of the samples derived from experimental sewage treatment system with a relative abundance of 9.9%. This group includes Burkholderia sp., which was on the other hand the most abundant genus in sample A and prevailed over their abundance in sample B (24.11% vs. 8.69%; Figure 8 ).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The copyright holder for this preprint (which this version posted April 1, 2023. ; https://doi.org/10.1101/2023.03.31.535185 doi: bioRxiv preprint halophilic and thermophilic environments, and their presence suggests that the Potomac river basin could be facing increased hydrological stress. Chloroflexi are known to be involved in organohalide respiration and has potential roles in the bioremediation of chlorinated compounds 24 -noted due to historic PCB pollution in the Chesapeake Bay region. [25][26][27][28] As these bacteria are able to survive in extreme conditions, this could mean that the river basin is subject to increased levels of pollution and other environmental stressors.…”
Section: Discussionmentioning
confidence: 99%